ANALISIS TINGKAT PERMINTAAN PEMBIAYAAN PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2006 – 2010 - Firdausiyah, Dewi Jannatul (Jurnal Ekonomi Pembangunan, 2011)
This study was a descriptive quantitative type of research which was conducted at 5 Islamic banks in Indonesia, entitled " The Level of Demand for financing Analysis at Islamic Banks in Indonesia Period 2006-2010?. From the results were obtained the coefficient of determination (R2) for panel data of regression model Random effect of 0.89. This means that the independent variables together were able to explain that 89% were variation in dependent variable, namely the financing demand. From the data analysis which had conducted simultaneously showed that the variable of income per capita and the profit sharing ratio had a more significant outcome of the financing demand than the variable of lending rates for working capital. It could be seen from the probability or significance level, which was variable of income per capita, profit sharing ratio,  and lending rates for working capital 0.0695: 0.0612 and 0.9438. Moreover, It could be seen from the F test, which F count > F table for 59.2 > 3.49.